2023
DOI: 10.3390/w15081631
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sand and Mixed Sand–Biochar Filters for Treatment of Road Runoff Quantity and Quality

Abstract: Nature-based solutions and similar natural water retention measures to manage urban runoff are often implemented by cities in order to reduce runoff peaks, catch pollutants, and improve sustainability. However, the performance of these stormwater management solutions is relatively rarely assessed in detail prior to their construction, or monitored and evaluated following implementation. The objective of this study was to investigate the field-scale performance of road runoff filters with respect to the managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Additionally, the sand and biochar mixture had a greater fraction of coarseand medium-grained particles compared to sand alone. Although, Koivusalo et al [51], reported that biochar amendment had no impact on the hydrologic performance of biofilters, Brown and Hunt [52] found that fine particles caused clogging and a reduction in permeability in modified bioretention systems. Results from these studies highlight the need to remove fine particles in bioretention media prior to construction.…”
Section: Hydraulic Performancementioning
confidence: 99%
“…Additionally, the sand and biochar mixture had a greater fraction of coarseand medium-grained particles compared to sand alone. Although, Koivusalo et al [51], reported that biochar amendment had no impact on the hydrologic performance of biofilters, Brown and Hunt [52] found that fine particles caused clogging and a reduction in permeability in modified bioretention systems. Results from these studies highlight the need to remove fine particles in bioretention media prior to construction.…”
Section: Hydraulic Performancementioning
confidence: 99%